How Canadians communicate IV : media and politics - Waddell, Christopher, 1952-; Taras, David, 1950-; Waddell, Christopher Robb (Athabasca University Press, 2012)
Substantial changes have occurred in the nature of political discourse over the past thirty years. Once, traditional media dominated the political landscape, but in recent years Facebook, Twitter, blogs and Blackberrys have emerged as important tools and platforms for political campaigns. While the Canadian party system has proved surprisingly resilient, the rhythms of political life are now very different. A never-ending 24-hour news cycle has resulted in a never-ending political campaign. The implications of this new political style and its impact on political discourse are issues vigorously debated in this new volume of How Canadians Communicate, as is the question on every politician’s mind: How can we draw a generation of digital natives into the current political dialogue?
14 Verbal Smackdown: Charles Adler and Canadian Talk Radio15 Contemporary Canadian Aboriginal Art: Storyworking in the Public Sphere; 16 Intimate Strangers: The Formal Distance Between Music and Politics in Canada; Final Thoughts: How Will Canadians Communicate About Politics and the Media in 2015?; Contributors; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; Y
Also available in print form.
English
Includes bibliographical references and index.
Description based on print version record.
Keywords: Mass media -- Political aspects -- Canada; Social media -- Political aspects -- Canada; Communication in politics -- Canada; Canada -- Politics and government; Social Media; Media; Politics